Nutritional and health impacts of religious and vegetarian foods - Haque, A. K. M. Ahasanul; Hashim, Nurhazirah; Yasmin, Farzana (Elsevier Publisher, 2018)
This chapter provides some forthcoming concept of religious foods and its importance to the nutritional and health of mankind. Besides, explanations of the concepts of food is clearly showed the benefits of all kinds of religious foods. In addition, understanding the nutritional and health impact religious and vegetarian food is one of the key discussions in this chapter. Moreover, the rationalization of religious food based on the aspects of nutrition will be discussed further. The chapter also points out that the most important objective of choosing religious and vegetarian food is ultimately on helping the consumer to practice a healthy lifestyle with balanced diet.